INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN FARMASI DI INDONESIA - Sriwahyuni, Diana; Hermawan, Sigit; Hanun, Nur Ravita (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2019)
This study aims to analyze the effects of Intellectual Capital to  Financial Performances of Pharmaceutical Company. Independent variable in this study is Intellectual Capital . Intellectual Capital which consist of Human Capital (HC), Structural Capital (SC), and the Capital Employed which uses a method Value Added Intellectual Coefficients (VAICTM.). Financial Company’s Performance is proxied by Return On Assest (ROA) and Net Profit Margin (NPM). This research samples are pharmaceutical company in the Indonesia Stock Exchange in 2011- 2015. Samples were collected by purposive sampling method and resulted in 7 firms as the samples. This study used simple linear regression to analyze data. The results of this study indicate that intellectual capital (IC) has effect on variable financial performance Return On Assets (ROA) and intellectual capital (IC) has effect on variable financial performance Net Profit Margin (NPM).